Estimation of Food Waste and Nutrient Loss in The Free Nutritious Meal Program for Students in East Aceh, Indonesia - Fatimah Zuhra; Ikeu Tanziha; Cesilia Meti Dwiriani; Muhammad Rizki Ramadhani (Journal of Health and Nutrition Research, 2026)
Food waste remains a major challenge in school meal programs, as it not only causes economic losses but also leads to resource inefficiency, and reduced nutritional benefits. This study aims to analyze differences in food waste amounts across free nutritious meal programs at the elementary, middle, and high school levels, estimate nutrient loss, and identify related factors of food waste among students in East Aceh Regency. A cross-sectional design was employed involving 106 students purposively selected from three schools participating in the free nutritious meal programs. Data were collected using a weighing method over a 10-day menu cycle, anthropometric measurements, structured interviews on student characteristics, and food preferences. Data were analyzed using the Kruskal-Wallis test, Pearson and Spearman correlations, and linear regression. The results showed that the average food waste was 24,3% of the served portion, with the highest amount in middle school (29,8%) and the lowest in high school (16,5%). The largest proportion of waste came from staple foods, vegetables, and plant-based side dishes. Nutrient loss due to food waste was equivalent to 12 complete lunch portions for a child per year. Factors significantly associated with food waste were age, gender, BMI-for-age, pocket money, and menu variety (p<0,05). Older students, males, who perceived the menu as more varied, tended to waste less food. These findings highlight the importance of portion adjustment, appropriate serving times, diversified menus, and nutrition education to reduce food waste and optimize the benefits of the Free Nutritious Meal program